Beneath These Red Cliffs - Holt, Ronald L. (Utah State University, University Libraries, 2006)
In this new and updated edition---with a foreword by Lora Tom, chairwoman of the Paiute Indian Tribe of Utah---Holt recounts the survival of a people against all odds. A compound of rapid white settlement of the most productive Southern Paiute homelands, especially their farmlands near tributaries of the Colorado River; conversion by and labor for the Mormon settlers; and government neglect placed the Utah Paiutes in a state of dependency that ironically culminated in the 1957 termination of their status as federally recognized Indians. The recognition and attendant services were not restored until 1980, but the act revived the Paiutes' identity, self-government, land ownership, and sense of possibility.